Petrographic and Geochemical Characteristics of Deccan Trap Basalts from Belagavi, Karnataka, India - Sachin R Kulkarni; Mahadeva M* (International Journal of Minerals, 2026)
The Deccan Trap volcanic province represents one of the largest continental flood basalt provinces in the world and provides significant insights into magma generation and evolution processes. The present study focuses on the petrography and geochemistry of basalts from the Belagavi region, which forms part of the southern extension of the Deccan volcanic province. Petrographic analysis of thin sections reveals that the basalts are mainly composed of plagioclase feldspar and augite, with minor opaque minerals. Various textures such as ophitic, sub-ophitic, glomeroporphyritic, intergranular, and intersertal textures are observed, indicating different stages of magma crystallisation. Geochemical analysis using X-ray Fluorescence Spectrometry (XRF) shows that the basalts are basic in composition with SiO₂ values ranging from 47.7–49.0 wt%. The TAS diagram classifies the samples within the basalt field, while the AFM diagram indicates their tholeiitic affinity. Trace element ratios further suggest similarities with the Mahabaleshwar formation lavas of the Deccan Traps.
Keywords: Belagavi basalts; Deccan traps; XRF analysis; geochemistry; large igneous province; petrography; tholeiitic Basalt